1997
DOI: 10.3168/jds.s0022-0302(97)76035-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Optimal Time of Insemination in Cows that Show Visual Signs of Estrus by Estimating Onset of Estrus with Pedometers

Abstract: An experiment was designed to estimate the optimal interval from the beginning of estrus to artificial insemination (AI). The data were analyzed by means of a mathematical model. The analysis was based on pedometer readings and results of rectal palpation at 42 to 49 d post-AI of 171 breedings in 121 cows. The chance of conception was highest between 6 and 17 h after increased pedometer activity; the estimated optimum was at 11.8 h. In this data file, the effects of disease, inseminator, time of AI (a.m. or p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
61
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 19 publications
7
61
2
2
Order By: Relevance
“…A previous study indicated that the optimal timing of insemination is 7 to 24 h before ovulation and that the best conception rate occurs when insemination takes place between 13 and 18 h before ovulation [19]. The results of recent studies showing detection of estrus in lactating cows using a pedometry system are in agreement with this previous study [20,21]. Insemination from a few hours to 20 h after pedometer estrus might produce a satisfactory pregnancy rate, at least for healthy heifers wearing leg pedometers under the paddock rearing conditions.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study indicated that the optimal timing of insemination is 7 to 24 h before ovulation and that the best conception rate occurs when insemination takes place between 13 and 18 h before ovulation [19]. The results of recent studies showing detection of estrus in lactating cows using a pedometry system are in agreement with this previous study [20,21]. Insemination from a few hours to 20 h after pedometer estrus might produce a satisfactory pregnancy rate, at least for healthy heifers wearing leg pedometers under the paddock rearing conditions.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, when cows were inseminated 8-12 h after the onset of the estrus, the conception rate was higher than that of cows inseminated at other times (P<0.05). Maatje et al [16] reported that the chance of conception was the highest between 6 and 17 h after increased pedometer activity; the estimated optimum was at 11.8 h. Our results were similar to the results of their study because the average AI time after the onset of estrus in pregnant cows was 12.0 h.…”
Section: Effect Of Estrus Duration and Time Of Ai On The Rate Of Concsupporting
confidence: 89%
“…In this study, when cows were inseminated 8-12 h after the onset of the estrus, the conception rate was higher than that of cows inseminated at other times (P<0.05). Maatje et al [16] reported that the chance of conception was the highest between 6 and 17 h after increased pedometer activity; the estimated optimum was at 11.8 h. Our results were similar to the results of their study because the average AI time after the onset of estrus in pregnant cows was 12.0 h.In conclusion, these results suggest that in the cows studied here, the postpartum BCS was remarkably low and that the functional recovery of reproduction was consequently delayed. Moreover, the results indicate that the estrus duration varied among individual cows.…”
mentioning
confidence: 99%
“…Therefore, these values are similar to the present results in Japanese Black cows: the ovulation time was 30.2 ± 0.6 h after the onset of pedometer estrus. Predicting ovulation time is useful for determining the optimal time of insemination for cows [4,7,18]. Our findings indicate that it is possible to predict ovulation time using the radiotelemetric pedometer (Experiment 1).…”
Section: Discussionmentioning
confidence: 73%